HIV/AIDS Research in Correctional Settings: A Difficult Task Made Even Harder? - Johnson, Mark E. (J Correct Health Care, 2015)
Housing a large number of individuals living with or at risk for HIV/AIDS, correctional settings have considerable potential for epidemiological, prevention, and treatment research. However, federal regulations and institutional challenges have limited the extent and types of such research with prisoners. This study examines the degree to which HIV/AIDS correctional researchers report greater challenges than do their non-correctional counterparts. Results indicated that correctional researchers reported significantly more frequent challenges than those in noncorrectional settings, even after controlling for experience; with the dominant difference related to challenges due to the research setting. These findings add empirical data and support previous research in the field; however, additional research should include correctional staff and incarcerated individuals, and explore whether these differences extend to other research topics.